Physical variables - lake temperature profile from Erssjön, Floating platform - Skogaryd Research Catchment (University of Gothenburg, 2025)
High frequency temperature profiles are measured in lakes of SITES Water to be able to determine the thermal structure.
Skogaryd Research Catchment (2025). Physical variables - lake temperature profile from Erssjön, Floating platform, 2016-10-11–2016-12-31 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/SRo2JB1eUkVYNAO4TwW0tzMx
Keywords: Skogaryd Research Catchment; Time instant; Time instant; Water temperature; Water temperature; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap